The Role of Jump Rope Game in Developing Early Childhood Cooperation Skills - Safitri, Dahrul (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – The proliferation of modern games has gradually eroded the existence of traditional games rich in essential cooperation values for children from an early age. This research aims to analyze the traditional jump rope game as a means to develop early childhood cooperation skills, amidst the prevalence of modern games that emphasize individualism. Design/methods/approach – This research employs a qualitative approach through a case study. Data collection involves observation, interviews, and documentation. The data analysis technique used follows Miles and Huberman's concept, including data reduction, data presentation, and conclusion drawing. The research informants consist of five parents of children aged 5-6 years, with three boys and two girls as research subjects. Data validity is ensured through source triangulation. Findings – The jump rope game, commonly known as